Teacher's Instructional Scaffolding in Teaching Writing Recount Text for Tenth Grade Students of SMAS Amir Hamzah Medan - Najwa Ramadhani Pane; Ariatna (International Journal of Language, Education, and Literature, 2025)
This study aimed to find the teacher’s instructional scaffolding in teaching writing recount text for tenth grade students of SMAS Amir Hamzah Medan, as well as the teacher’s reasons for implementing it. This study utilized the theory of Walqui (2006 which outlines six types of instructional scaffolding: modelling, bridging, contextualizing, schema building, re-presenting text, and developing metacognition. Data were collected through observation and interview. The researcher employed the data analysis model of Miles et al. (2014), which consists of three stages: data condensation, data display, and drawing and verifying conclusions. This study revealed that (1) The teacher implemented five out of six types of instructional scaffolding proposed by Walqui (2006), namely modelling, bridging, contextualizing, schema building, and developing metacognition. (2) There were seven teachers’ reasons for implementing the five types of instructional scaffolding such as supporting understanding and accuracy, activating prior knowledge and motivating students, advancing student’s interest and providing supporting media, improving student’s awareness and linking the previous material with the material being taught, enhancing self-reflection, collaboration, critical thinking, communication skills, and creating a conducive learning environment.